2010
DOI: 10.1007/s12223-010-0062-1
|View full text |Cite
|
Sign up to set email alerts
|

Variability of treponemes in the rumen of ruminants

Abstract: Complete 16S rRNA sequences were determined of recently proposed new species of treponemes designated strain S and T. Sequence comparison indicated that both species belong to the Treponema saccharophilum cluster, having thus at least 5 cultivable representatives. Phylogenetic analysis of available GenBank 16S rRNA sequences revealed two phylogenetically distant treponema clusters (T. saccharophilum cluster and T. bryantii cluster). Surprisingly, while among cultivated treponemes dominate T. saccharophilum clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Treponema has been estimated to account for less than 2.4% of the bovine rumen bacterial community (Sikorová et al , 2010), but as described above, our results suggest that species of this genus are more abundant in the moose rumen. All MAGs of phylum Spirochaetes were of genus Treponema and resembled closely with Treponema saccharophilum, a pectinolytic bacterium isolated from bovine rumen (Paster and Canale-Parola, 1985).…”
Section: Resultssupporting
confidence: 62%
“…Treponema has been estimated to account for less than 2.4% of the bovine rumen bacterial community (Sikorová et al , 2010), but as described above, our results suggest that species of this genus are more abundant in the moose rumen. All MAGs of phylum Spirochaetes were of genus Treponema and resembled closely with Treponema saccharophilum, a pectinolytic bacterium isolated from bovine rumen (Paster and Canale-Parola, 1985).…”
Section: Resultssupporting
confidence: 62%
“…A meta‐analysis of available data conducted by Sikorova et al . () revealed that the Treponem a genus represented < 2.4% of total rumen bacteria.…”
Section: Resultsmentioning
confidence: 98%
“…Prior to this study, only one 16S rRNA gene sequence (accession number ), with 98% similarity to T. saccharophilum , had been deposited in the GenBank database. The lack of T. saccharophilum‐ like 16S rRNA gene sequences in the available databases or published studies has been recognized in recent papers (Sikorova et al ., ; Bekele et al ., ). One possible explanation is that the Treponema genus was not well discussed due to its relative low abundance.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations